Anthropometry profile of Olympic singles badminton players - Blanca-Torres, J.; Cabello-Manrique, D.; Fernández-Garcia, A. I.; Kondric, M. (Science and Racket Sports VI, 2019)
The aim of this study was to analyse the profile of singles elite badminton player in Olympic Games. 167 singles badminton players (81 male and 86 female) were selected. The players were the best in the world at that time. Age (months), height (m), mass (kg) and BMI (kg/m2) were determined with their ranking position (top5 to top>46) in London 2012 and Rio de Janeiro 2016. The results shown similar characteristics in the different variables along the ranking position. In male, there is an increase in age at the top, and in RIO there are few or no participants among top-20 to top-30. There are not differences in the anthropometrics characteristics. In female, the values are very similar along the ranking and Olympic Games. In conclusion, there are no descriptive differences in the general profile of the badminton player throughout his position in the ranking.